If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -52) + (2x + -18) = 180 Reorder the terms: (-52 + 4x) + (2x + -18) = 180 Remove parenthesis around (-52 + 4x) -52 + 4x + (2x + -18) = 180 Reorder the terms: -52 + 4x + (-18 + 2x) = 180 Remove parenthesis around (-18 + 2x) -52 + 4x + -18 + 2x = 180 Reorder the terms: -52 + -18 + 4x + 2x = 180 Combine like terms: -52 + -18 = -70 -70 + 4x + 2x = 180 Combine like terms: 4x + 2x = 6x -70 + 6x = 180 Solving -70 + 6x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '70' to each side of the equation. -70 + 70 + 6x = 180 + 70 Combine like terms: -70 + 70 = 0 0 + 6x = 180 + 70 6x = 180 + 70 Combine like terms: 180 + 70 = 250 6x = 250 Divide each side by '6'. x = 41.66666667 Simplifying x = 41.66666667
| 280=x+2 | | y=(sqrt(16x^2)+5x+16) | | 96+2x=8 | | w(x)=-2x^2-2 | | am-d=b | | 72+2x=8 | | u(x)=2x+1 | | 48+2x=8 | | 12x+16=46+2 | | 24+2x=8 | | 5z+11=7y | | 2u^2+14u+25=(u+2)(u+2) | | 2(x+36)=3(x+12) | | 15p+7=q | | 7x+11=7-2x | | -7y=-2x | | 0.78x=42 | | (4x-52)(2x-18)=180 | | 10q+7q=r | | -7y=0-2x | | 0+2x=8 | | 3x+8*4=80 | | -24+2x=8 | | 4x^2+y^2=49 | | 7(m+9)=4n | | -49x^2+12x=0 | | 6mn+3p=14 | | (7+w)(5w+8)=0 | | 4.5t^2+10t=0 | | 2sin^2x-sinx-3=0 | | 1+3w-7=4w-7 | | 4xsquare+52x-120=0 |